Navigated minimally invasive puncture of the trigeminal cistern in horses—a cadaveric study in preparation for a controlled rhizotomy - de Preux, Mathieu; Precht, Christina; Becker, Richard; Stieglitz, Lennart; Easley, Jeremiah; Koch, Christoph (Frontiers in Veterinary Science, 2025)
IntroductionTrigeminal-mediated headshaking is a neuropathic disorder in horses, characterized by signs of regional pain similar to trigeminal neuralgia in humans. The injection of glycerol into the trigeminal cistern to ablate pain-conducting nerve fibers within the trigeminal ganglion -known as glycerol rhizotomy- is a well-established treatment in human medicine. This study compares two approaches to the equine trigeminal cistern using a navigation system for guiding needle placement, a previously described ventral and a newly developed transmandibular lateral approach. The surgical accuracy and risk of iatrogenic collateral damage for the two approaches are assessed.Materials and methodsFive equine cadaveric specimens were used in this study. Magnetic resonance imaging (MRI) of the target region was performed using a 3 T MRI, followed by cone beam computed tomography (CBCT). The two datasets were fused in a surgical navigation system. A trajectory for a ventral navigated approach (VNA) to the trigeminal cistern was planned on one side and for a transmandibular lateral navigated approach (TLNA) on the contralateral side, using the system’s planning function. The trigeminal cistern was punctured after introducing the needle along the planned trajectory under real-time navigation guidance, and a toluidine blue solution was injected. A titanium rod was then inserted as a stylet to place a titanium seed within the trigeminal cistern. The rod was left in place to allow artifact-free postprocedural assessment of the surgical trajectory and to measure surgical accuracy aberration (SAA). Prior to dissection, an endoscopic examination was performed to identify any potential perforation of the guttural pouches.ResultsSuccessful puncture of the trigeminal cistern was achieved in 5/5 specimens via the TLNA, with a median SAA of 3.92 mm (range 3.42 mm - 4.55 mm) and in 3/5 specimens via the VNA, with a median SAA of 6.45 mm (range 2.89 mm - 10.85 mm). The VNA resulted in iatrogenic injury to the internal carotid artery in two cases, and the linguofacial artery in another case. Focal perforation of the mucosa of the guttural pouch was observed in one specimen injected via TLNA.ConclusionThe TLNA enables accurate and precise minimally invasive puncture of the equine trigeminal cistern in an experimental setting.